Blood Sampling From Rat Ileal Mesenteric Vein Revealed a Major Role of Dietary Protein in Meal-Induced GLP-1 Response - Hira, Tohru; Sekishita, Madoka; Hara, Hiroshi (Frontiers in Endocrinology, 2021)
The present study was conducted to examine region-dependent glucagon-like peptide-1 (GLP-1) responses to “meal ingestion” under physiological (conscious and unrestrained) conditions using rats with a catheter inserted into either the portal vein (PV) or the ileal mesenteric vein (ILMV). After recovery from the cannulation surgery, blood samples were collected from either PV or ILMV catheter before and after the voluntary ingestion of test diets. After a AIN-93G standard diet ingestion, GLP-1 concentration was higher in ILMV than in PV, and postprandial responses of peptide-YY (PYY) had similar trend, while that of glucose dependent-insulinotropic polypeptide showed an opposite trend to GLP-1/PYY responses. In a separated experiment, a protein-enriched diet containing casein at 25% wt/wt transiently increased GLP-1 concentration only in ILMV; however, a protein-free diet did not increase GLP-1 concentrations in PV or ILMV. These results indicate that postprandial GLP-1 is immediately released from the distal intestine under physiological conditions, and that dietary protein has a critical role in the enhancement of postprandial GLP-1 response.